Superhero Movie: Breaking the challenges of topics in the modern epos - Akim, Kamila; Kara-Murza, Georgy; Saenko, Natalya; Suharyanto, Agung; Kalimullin, Dilovar (Opción, 2019)
The purpose of this study is to determine whether the collective unconscious always has irrational fears or unconsciousness - the most rational actor in modern times via comparative qualitative research methods. As a result, mythological consciousness creates the image of a protector and in this image there is an immanent image of the threat from which a little person wants to find a protector. In conclusion, when viewer forget the current heroes and love others, fundamentally others, this will mean that tectonic shifts have occurred again in the public consciousness and new times come.